A self-stabilizing ( Δ + 4 )-edge-coloring algorithm for planar graphs in anonymous uniform systems - Tzeng, Chi-Hung; Jiang, Jehn-Ruey; Huang, Shing-Tsaan (Information processing letters, 2007)
This paper proposes a self-stabilizing edge-coloring algorithm using ( Δ + 4 ) colors for distributed systems of a planar graph topology, where Δ ⩾ 5 is the maximum degree of the graph. The algorithm can be applied to anonymous uniform systems and its time complexity is O ( n 2 ) moves under the central daemon model.